A dynamic concept of animal welfare: The role of appetitive and adverse internal and external factors and the animal’s ability to adapt to them - Arndt, Saskia S.; Goerlich, Vivian C.; van der Staay, F. Josef (Frontiers in Animal Science, 2022)
Animal welfare is a multifaceted issue that can be approached from different viewpoints, depending on human interests, ethical assumptions, and culture. To properly assess, safeguard and promote animal welfare, concepts are needed to serve as guidelines in any context the animal is kept in. Several different welfare concepts have been developed during the last half decade. The Five Freedoms provided the basis for developing animal welfare assessment tools, the Five Domains concept guide those responsible for safeguarding animal welfare, while the Quality of Life concept focuses on how the individual perceives its own welfare state. Here, we propose a modified and extended version of an earlier animal welfare concept - the Dynamic Animal Welfare Concept (DAWCon) - based on the adaptability of the animal, taking the importance of positive emotional states and the dynamic nature of animal welfare into account: An individual is likely in a positive welfare state when it is mentally and physically capable and possesses the ability and opportunity to react adequately to sporadic or lasting appetitive and adverse internal and external stimuli, events, and conditions. Adequate reactions are elements of an animal’s normal behavior. They allow the animal to cope with and adapt to the demands of the (prevailing) environmental circumstances, enabling it to reach a state that it perceives as positive, i.e., that evokes positive emotions. This paper describes the role of internal as well as external factors influencing welfare, exerting their effects in a sporadic or lasting manner. Behavior is high-lighted as crucial read-out parameter. As most animals under human care are selected for certain traits that may affect their behavioral repertoire it is crucial to have thorough ethograms, i.e., a catalogue of specific behaviors of the species/strain/breed under study. DAWCon highlights aspects that need to be addressed when assessing welfare and may stimulate future research questions.